The Correlation between Listening Habits to English Songs and Vocabulary Mastery of the First Year English Study Program Students of FKIP Universitas Riau - Fitri, Risha Rahma; Syarfi, M; Supriusman, Supriusman (Indonesian Journal of Education and Development Research, 2025)
This research investigates the correlation between listening habits to English songs and vocabulary mastery of the first-year English Study Program students of FKIP Universitas Riau. English songs are increasingly popular and serve as an engaging medium for language learning, offering repeated exposure to new vocabulary, improved pronunciation, and contextual understanding of words. Students with developed listening habits to English songs are less likely to feel unfamiliar with new vocabulary due to frequent exposure. This study employed a quantitative method with a correlational design, utilizing a questionnaire and vocabulary test for data collection. The Pearson Product-Moment formula, processed via SPSS, revealed a correlation coefficient of 0.714, indicating a high correlation. The null hypothesis (Ho) was rejected, confirming a significant relationship between the two variables. These findings underscore that there is a high correlation between listening habits to English songs and vocabulary mastery of the first year English Study Program students of FKIP Universitas Riau.